Os caminhos da “Quase memória” em Nancy Huston e Carlos Heitor Cony - Rocha, Vanessa Massoni da (Letras de Hoje, 2015)
Este trabalho propõe uma reflexão sobre a escrita memorialística no romance canadense Cantique des plaines, de Nancy Huston, de 1993 e no romance brasileiro Quase memória, de Carlos Heitor Cony, de 1995. Trata-se de privilegiar na tessitura dos romances o binômio ‘memória e morte’ e investigar o papel incontornável da memória como elo espaço-temporal entre avós, pais e filhos. Neste sentido, contemplaremos as relações entre a escrita, o luto e os diálogos entre o lembrar e o esquecer. ********************************************************************************************************************************************************************************************************************* The paths of “Almost memory” in Nancy Huston and Carlos Heitor Cony Abstract: This paper proposes a reflection on the writing of the memory in Canadian novel Cantique des plaines, by Nancy Huston, 1993 and in the Brazilian novel Almost memory, by Carlos Heitor Cony, 1995. We prioritize in the writing of novels the binomial ‘memory and death’ and investigate the inescapable role of memory as spatio-temporal link between grandparents, parents and children. In this sense, we will contemplate the relationships between writing, the mourning and the dialogues between remembering and forgetting. Keywords: Written from memory; “Almost memory”; Nancy Huston; Carlos Heitor Cony; Canadian literature; Brazilian literature